Developing solutions for pay-as-you-throw information systems - Barraca, J.P. (2020)
The development of pay-as-you-throw (PAYT) systems – one of the strategies behind smart waste concepts – has a large set of challenges from the information technology (IT) point of view. The diversity of existing charging models in different towns already poses a complexity problem for a single universal IT solution. The situation is even more complex as the diversity of pay-as-you-throw systems is very large, with different tariffs and different objectives. This paper describes the development of an information system for supporting multiple approaches for PAYT systems and describes its implementation in the context of a European project. The design strategy and the use of best practices lead to a scalable and effective PAYTspecific Information System that has proved itself able to support a diversity of requirements across south Europe.